Photodynamic inactivation of Staphylococcus aureus with rose bengal reduces superantigen activity - Ogonowska, Patrycja; Kobiela, Adrian; Hulacka, Anna; Gutowska-Owsiak, Danuta; Nakonieczna, Joanna (Frontiers in Immunology, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder marked by barrier dysfunction and immune dysregulation. Colonization of lesional skin by Staphylococcus aureus, present in up to 80–100% of cases, exacerbates inflammation, in part through production of superantigenic toxins. While standard treatments such as topical corticosteroids, antibiotics, and antiseptic baths are widely used, their outcomes remain variable and often inadequate, highlighting the need for alternative strategies that minimize adverse effects and resistance development. In this study, we evaluated antimicrobial photodynamic inactivation (aPDI) using rose bengal (RB), a photosensitizer activated by visible light, as a potential approach to reduce S. aureus colonization and virulence. Across in vitro, ex vivo, and murine in vivo models, RB-mediated aPDI significantly decreased S. aureus viability and markedly attenuated the expression and activity of staphylococcal enterotoxins. Transcript and protein analyses confirmed substantial reductions in superantigenic activity post-aPDI. These effects were dependent on the combination of both RB and light, with no significant impact observed with either component alone. Our findings indicate that RB-based aPDI may represent a promising non-antibiotic approach to limit S. aureus viability and toxin activity in the context of AD. Our data contribute to the understanding of how photodynamic inactivation affects S. aureus virulence and highlight a model for studying the impact of microbial factors on skin immune responses in AD.